Genetic variants in adult liver diseases - Dröge, C.; Häussinger, D.; Keitel, V. (Zeitschrift für Gastroenterologie, 2015)
In the last decades, understanding of genetic variants contributing to liver disease development has considerably improved through novel genotyping techniques. Genetic variants of single genes are known to be decisive for the development of monogenetic liver diseases of varying severity. Identification of genetic variants is an important part of the diagnostic process, e. g. the majority of patients with high iron [Fe] (HFE)-associated hemochromatosis carry the homozygous mutation p.C282Y. Detection of mutations in genes encoding hepatobiliary transport proteins like familial intrahepatic cholestasis 1 (FIC1), bile salt export pump (BSEP), or multidrug resistance protein 3 (MDR3) is the basis to differentiate various forms of intrahepatic cholestasis. Moreover, genetic variants in a variety of genes are known to act as disease modifiers and represent risk factors for disease progression and the development of cirrhosis or even hepatocellular carcinoma. Success of drug treatment or appearance of severe side effects can also be influenced by specific genetic variants. All these aspects underscore the increasing importance of genetic variants, which in the future may help to identify patients at risk for disease progression or help to guide treatment decisions. In the present overview, specific frequent genetic variants are summarized that play roles in monogenetic liver diseases, forms of intrahepatic cholestasis, gallstone development, fatty liver disease, drug-induced liver injury, and liver disease progression as well as hepatocellular carcinoma development.
Keywords: monogenetisch; Polymorphismus; autosomal; Genotyp; Phänotyp; Krankheitsmodifikator